THE ANALYSIS OF THE AREAS OF POPULATION GROWTH OF KASHKADARYA REGION (Journal of Universal Science Research, 2023)
In this article, socio-economic, demographic factors, oasis demography, population growth from other regions of the republic in Kashkadarya region for the years 1991-2021, decrease in birth rate and birth rate, changes in population density and location, increase in average life expectancy, growth of urban population in rural areas issues of slowing down of population, activation of migration are analyzed on the basis of archival sources and statistical data.